If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 23 + 12 = 9 Reorder the terms: 23 + 12 + 2x = 9 Combine like terms: 23 + 12 = 35 35 + 2x = 9 Solving 35 + 2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 2x = 9 + -35 Combine like terms: 35 + -35 = 0 0 + 2x = 9 + -35 2x = 9 + -35 Combine like terms: 9 + -35 = -26 2x = -26 Divide each side by '2'. x = -13 Simplifying x = -13
| 7*x+3=42 | | y^4+36=0 | | 13+13p+10=23+3p | | 5(X+3)-2=3 | | 4=2(x-3)-2 | | 3.5x=-4.9 | | 45x+40x=55 | | x-2y+4x=10 | | s/3+4=6 | | x^2+y^2+2x-y+1=0 | | 153=x-11 | | 19-2+21=X-2 | | -9 = w5 | | c+-5=4 | | 9m-8m+20=87 | | -3=s-4 | | F(x)=4x^3-36x | | -13+5=X+9 | | -.07x+7.56=-0.3x+5.56 | | -3 = s-4 | | 19=4j-1 | | x+3.7=10.8 | | q+-25=3 | | 4(7-3x)+2x=108 | | 16=4f | | X-21=-36 | | x^2+2xyi-y^2=i | | 2+8(7-x)=82 | | (9x-2)+(x^2y+7)+6x+(x^2-9)=0 | | 3y+1=-10 | | Ax+bn=c | | 4.603y-1.842=-3.641 |